2023
DOI: 10.3390/app132112004
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Dropout Prediction for University Students Using Machine Learning

Choong Hee Cho,
Yang Woo Yu,
Hyeon Gyu Kim

Abstract: Student dropout is a serious issue in that it not only affects the individual students who drop out but also has negative impacts on the former university, family, and society together. To resolve this, various attempts have been made to predict student dropout using machine learning. This paper presents a model to predict student dropout at Sahmyook University using machine learning. Academic records collected from 20,050 students of the university were analyzed and used for learning. Various machine learning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In binary scenarios, researchers meticulously define the thresholds for high class imbalance, typically when the minority class constitutes less than 8% of the dataset [17,20,21,23,25] while acknowledging imbalance when the minority class falls below 35% [18,31]. For example, in a recent study, a random split allocated 85% of the dataset to training data, revealing a distribution of 53.38% for on-time graduations and 46.62% for late graduations [11].…”
Section: Number Of Minority Class In Class Imbalancementioning
confidence: 99%
See 3 more Smart Citations
“…In binary scenarios, researchers meticulously define the thresholds for high class imbalance, typically when the minority class constitutes less than 8% of the dataset [17,20,21,23,25] while acknowledging imbalance when the minority class falls below 35% [18,31]. For example, in a recent study, a random split allocated 85% of the dataset to training data, revealing a distribution of 53.38% for on-time graduations and 46.62% for late graduations [11].…”
Section: Number Of Minority Class In Class Imbalancementioning
confidence: 99%
“…Nevertheless, SMOTE has shown promising results in terms of Area Under the Curve (AUC), with predictive models achieving the highest AUC of 69% compared to other class imbalance techniques when dealing with minority class instances as low as 4.7% [23]. Additionally, predictive models enhanced with SMOTE have demonstrated the highest average F1-score of 76.20% after implementing feature selection with Pearson correlation [25]. Moreover, in their study, researchers observed an improvement in average recall from 75.20% to 88.20% by increasing the number of minority class instances through SMOTE.…”
Section: Class Imbalance Treatment Techniques In Mitigating Class Imb...mentioning
confidence: 99%
See 2 more Smart Citations